Literature Review on Single and Twin-Screw Extruders Design for Polymerization Using CFD Simulation - Elham Delvar; Inês Oliveira; Margarida S. C. A. Brito; Cláudia G. Silva; Arantzazu Santamaria-Echart; Maria-Filomena Barreiro; Ricardo J. Santos (Fluids)
This work presents a comprehensive review of the evolution in modeling reactive extrusion (REx), tracing developments from early analytical models to advanced computational fluid dynamics (CFD) simulations. Additionally, it highlights the key challenges and future directions in this field. Analytical models to describe the velocity profiles were proposed in the 1950s, involving certain geometrical simplifications. However, numerical models of melt polymeric flow in extruders have proven to be crucial for optimizing screw design and predicting process characteristics. The state-of-the-art CFD models for single and twin-screw extruders design address the impact of geometry (type of mixing elements and geometrical simplifications of CFD geometries), pressure and temperature gradients, and quantification of mixing. Despite the extensive work conducted, modeling reactive extrusion using CFD remains challenging due to the intricate interplay of mixing, heat transfer, chemical reactions, and non-Newtonian fluid behavior under high shear and temperature gradients. These challenges are further intensified by the presence of multiphase flows and the complexity of extruder geometries. Future advancements should enhance simulation accuracy, incorporate multiphase flow models, and utilize real-time sensor data for adaptive modeling approaches.